2018
DOI: 10.1016/j.resuscitation.2017.12.022
|View full text |Cite
|
Sign up to set email alerts
|

Postanoxic alpha, theta or alpha-theta coma: Clinical setting and neurological outcome

Abstract: Hypoxic-ischemic AC, TC and ATC are associated with a poor prognosis and a high rate of mortality. In younger patients with AC, TC and ATC and incomplete forms showing reactivity on the EEG, there is a greater probability of clinical recovery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 34 publications
0
7
0
Order By: Relevance
“… GOS at 1,5 years Auditory + nociceptive and/or tactile + visual Li et al (2018) [ 65 ] CA/H 73 EEG-R predicted survival with OR = 8.75 (1.48–51.95), p = 0.017. 82.1 84.1 86.8 78.7 GOS at 6 months Fernández-Torre et al (2018) [ 57 ] CA/H 26 In patients with a diagnosis of postanoxic alpha coma, theta coma, or alpha-theta coma, there was increased association of EEG-R with survival ( p = 0.07). CPC at 5 months Fantaneanu et al (2016) [ 56 ] CA/H (TH) 60 EEG-R varies depending on the stimulus modality as well as the temperature.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… GOS at 1,5 years Auditory + nociceptive and/or tactile + visual Li et al (2018) [ 65 ] CA/H 73 EEG-R predicted survival with OR = 8.75 (1.48–51.95), p = 0.017. 82.1 84.1 86.8 78.7 GOS at 6 months Fernández-Torre et al (2018) [ 57 ] CA/H 26 In patients with a diagnosis of postanoxic alpha coma, theta coma, or alpha-theta coma, there was increased association of EEG-R with survival ( p = 0.07). CPC at 5 months Fantaneanu et al (2016) [ 56 ] CA/H (TH) 60 EEG-R varies depending on the stimulus modality as well as the temperature.…”
Section: Resultsmentioning
confidence: 99%
“…Kaplan et al concluded that, although the cause of alpha coma largely predicted outcome, EEG-R predicted survival because most patients with EEG-R awoke, whereas most of those without EEG-R died [ 44 ]. Fernández-Torre et al showed that in 26 patients with a diagnosis of postanoxic alpha coma, theta coma, or alpha-theta coma, EEG-R was associated with survival ( p = 0.07) [ 57 ]. In 2009, Rossetti et al found that postanoxic status epilepticus patients with favorable outcome exhibited preserved brainstem reflexes, cortical somatosensory evoked potentials (SSEPs), and reactive EEG background [ 18 ].…”
Section: Resultsmentioning
confidence: 99%
“…Firstly, despite the background continuity of the alpha or theta activity on EEG, specific coma patterns known as the alpha and theta comas with monotonous, invariable frontal predominance rhythms were also differentiated from the alpha and theta activities [23]. These EEG findings indicate an unfavourable prognosis [23]. Secondly, the restoration timing is another important factor.…”
Section: The Prognostic Value Of Background Eeg Frequencymentioning
confidence: 99%
“…This 60-year male patient had predominant theta waves on his EEG without an initial shockable rhythm. Many previous studies demonstrated that young CA survivors had a higher likelihood for neurological recovery, despite their presumed unfavourable prognosis, and therefore WLST should be carefully considered for CA survivors of a young age [23,26,27].…”
Section: Other Clinical Prognostic Factors Combined With Eeg Findingsmentioning
confidence: 99%
“…This elevation of theta oscillations is induced by direct damage to the brainstem, diffuse axonal damage, or other etiologies, including cerebral hypoxia [ 51 , 52 ]. Further, continuous theta rhythm had been associated with poor outcomes [ 53 ]. In our study, the decrease of the theta-band PSD was found in patients with a better outcome, which could be a marker of their preserved sensitivity to tactile stimulation.…”
Section: Discussionmentioning
confidence: 99%